Bioactivity of a Family of Chiral Nonracemic Aminobenzylnaphthols towards Candida albicans - Maria Annunziata M. Capozzi; Cosimo Cardellicchio; Angela Magaletti; Antonio Bevilacqua; Marianne Perricone; Maria Rosaria Corbo (Molecules, 2014)
Chiral nonracemic aminobenzylnaphthols were obtained by a Betti multi-component reaction between 2-naphthol, aryl aldehydes and enantiopure arylethylamine. Moreover, some new aminobenzylnaphthols were synthesized by a similar reaction between 2-naphthol, aryl aldehydes and prolinol. These aminobenzylnaphthols, synthesized from different components and thus having different structural features, were tested as anti-yeast agents inhibiting Candida albicans. The effect towards the test strain was studied with a microdilution approach and three different concentrations (150, 300 and 450 µg/mL) were tested. The best results were found for the aminobenzylnaphthols obtained from 1-naphthylethylamine and from natural prolinol. The use of the two-way ANOVA highlighted the better performances of the prolinol derivative among the differently structured aminobenzylnaphthols that were screened. The activity towards C. albicans of this prolinol derivative resulted to be interesting and could represent a promising alternative to overcome the problem of the strains resistant to the traditional antifungals.